Investigasi tegangan kerja pada pisau pencacah di mesin shredder-extruder dalam satu penggerak utama menggunakan Metode Elemen Hingga - Adriyan Adriyan; Sufiyanto Sufiyanto; Marfizal Marfizal (Universitas Muhammadiyah Metro, 2023)
Plastic flakes from shredding processes are produced by tearing plastic wastes using shredder blades. During the shredding process, tear forces are the source of loading acting on the tip of the shredder blades. Hence, this research is performed to investigate the working stresses on the blades when subjected to the tear forces during the shredding process. Thus, the working stresses on those blades can be computed by applying the finite element method. In this research, the blades are modeled by two kinds of finite elements, namely the triangular plane stress element and tetrahedron element, with linear shape functions. As a result, the maximum stresses on the blades lie within the range of 49 to 52 MPa for both models. These maximum working stress are below the yield strength of the material used for manufacturing those blades, i.e.: ASTM A36 with 250 MPa of yield strength. Overall, it can be concluded that there are no significant discrepancies in the computed working stresses among the blades.